Invariant measures for discrete dynamical systems and ergodic properties of generalized Boole-type transformations - Blackmore, D.; Golenia, J.; Prykarpatsky, A. K.; Prykarpatsky, Ya. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Invariant ergodic measures for generalized Boole-type transformations are studied using an invariant quasimeasure generating function approach based on special solutions for the Frobenius - Perron operator. New two-dimensional Boole-type transformations are introduced, and their invariant measures and ergodicity properties are analyzed.